Urban Studies Border and Mobility: Proceedings of the 4th International Conference on Urban Studies (ICUS 2017), December 8-9, 2017, Universitas Airlangga, Surabaya, Indonesia - Kerr , Thor; Ndimande, Bekisizwe; Van der Putten, Jan; Johnson-Mardones, Daniel F.; Ariani Arimbi, Diah; Sari Amalia, Yuni (Taylor & Francis, 2019)
This work contains a selection of papers from the International Conference on Urban Studies (ICUS 2017) and is a bi-annual periodical publication containing articles on urban cultural studies based on the international conference organized by the Faculty of Humanities at the Universitas Airlangga, Indonesia. This publication contains studies on issues that become phenomena in urban life, including linguistics, literary, identity, gender, architecture, media, locality, globalization, the dynamics of urban society and culture, and urban history.